Optimised robot calibration using a vision-based measurement system with a single camera - Motta, J. M. S. T. (Cranfield University, 1999)
Robot calibration plays an increasingly important role in robot production as well as in robot operation and integration within computer integrated manufacturing or assembly systems. The production, implementation and operation of robots are issues where robot calibration results can lead to significant accuracy improvement and/or cost- savings. The thesis describes techniques for modelling, optimising and performing robot calibration processes using a 3-D vision-based measurement system for off-line programming. The identification of the nonrlnal kinematic model is optimised using numerical methods to eliminate redundant geometric parameters in the model. Calibration based on the optimised model shows improvement in robot accuracy when compared to the non-optimised model. The basics of the measurement system consist of a single CCD camera mounted on the robot tool flange, image processing software, and algorithms specially developed to measure the end-effector pose relative to a world coordinate system. Geometric lens distortions are included in the analytical technique. The target consists of two identical clusters of calibration points printed on photographic paper, and mounted on the sides of a 90-degree angle plate. Experimental work was performed to assess the measurement system accuracy at different distances from the camera to the target. An average accuracy from O.2mm to O.4mm was obtained at distances between 6S0mm to 9S0mm. Tests were also performed on three different robots to assess the improvement in the overall robot accuracy. The robots tested were: PUMA-SOO, IRB-2400 and IRB-6400. The errors before calibration for the three robots were approximately in a range from Smm to lSmm if measured in a large volume. The best average accuracy obtained after the calibration of the three robots was O.3Smm, O.60mm and O.4Smm respectively. This study shows that many different variables are involved in the calibration process. The influence of these variables was studied both experimentally and by means of simulation.